Financial and Credit Regulation as a Tool for Attracting Investments in Tourism and the Hotel and Restaurant Business of Ukraine - Kampo, Ilda; Kulinich, Tetiana; Ivanov Аndrii; Biletska, Natalia; Mashika, Hanna (International Journal of Economics and Financial Issues, 2024)
This research investigates into the significant role of financial and credit regulations in promoting investments within Ukraine’s tourism sector, with a specific emphasis on the hotel and restaurant industry. By integrating mathematical modelling and empirical data analysis, the study uncovers how regulatory environments and credit accessibility jointly influence investment decisions. The development of a differential equation model quantitatively reveals that measures aimed at regulatory simplification and enhancing credit conditions are closely linked with increased investment levels. It identifies critical thresholds for regulatory simplification and credit availability, where indices exceeding 0.45 and 0.55, respectively, are associated with substantial growth in investment rates. This assertion is substantiated by empirical evidence from a survey of 250 industry stakeholders, highlighting the significant positive effects of these regulatory and financial adjustments on investment intentions. The findings highlight the necessity of precise financial and credit regulatory reforms to improve Ukraine’s tourism investment climate. The practical significance of this research lies in its potential to guide policy formulation aimed at unlocking the investment potential of Ukraine’s tourism sector, ensuring its growth and sustainability in the global context.